Analisa Pengaruh Corporate Social Responsibility, Leverage dan Likuiditas Terhadap Kebijakan Deviden - Verara, Ayudiaz Bella; Nyale, M Hendri (Ikatan Da'i Indonesia, 2024)
The mining industry is an important industry for the government, and the development of stock dividends in the mining sector is quite volatile, where the smaller the profit generated, the smaller the stock dividends obtained. Dividend policy is a component that cannot be separated from the interests of management and shareholders. The purpose of this study was to determine the effect of corporate social responsibility (CSR), leverage, and liquidity on the company's dividend policy. This study applies quantitative method. The CSR variable is measured using the GRI Standard indicator, the leverage variable is measured using the debt equity ratio (DER), the liquidity ratio is measured using the current ratio (CR), and the dependent variable, namely dividend policy, is measured using the dividend payout ratio (DPR). This study uses secondary data sources, namely annual financial reports, and purposive sampling as a sampling technique. The data were analysed using multiple linear regression analysis. The results of the study revealed that there was a positive but not significant effect between the CSR variable and dividend policy, the leverage variable had a positive effect on dividend policy; and the liquidity variable had an effect on dividend policy. This research is expected to be useful as a source of information in the learning process and also to gain deeper knowledge about the effect of corporate social responsibility, leverage, and liquidity on dividend policy in manufacturing companies in the mining and energy industry sectors that are listed on the IDX for 2020–2022.